A Desain Program Diklat Berbasis Identifikasi Kebutuhan dan Tujuan Organisasi: Studi Pustaka - Rafiuddin, Moh.; Listiana, Heni; Atiqullah, Atiqullah (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
This study aims to theoretically describe the design of training programs. Using the library research method, this study is expected to provide a detailed explanation of its objectives. The findings indicate that the implementation of training programs involves several key stages, starting from identifying training needs that focus on skill gaps and organizational goals to designing and evaluating training programs. Training programs should be designed to meet the specific needs of participants and training objectives while considering available resources. Therefore, training design includes selecting relevant materials and setting clear goals. Effective training should demonstrate the relationship between educational theory and training practices, analyze training needs, and ensure follow-up actions that enhance the management of education and training programs. Thus, a training program design based on the identification of needs and organizational objectives can improve training effectiveness, ensure goal achievement, and support the optimal development of participants' competencies.